Hukum Internasional dalam Perlindungan Hak Asasi Manusia di Era Digital - Triadi, Irwan; Cahyono, Marsha Putri (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2025)
The digital era has brought inevitable changes to human life, changing the way we communicate, interact, and access information. Digital space has become a new public space where individuals can express themselves, access information, and participate in public life. However, this digital space is also vulnerable to human rights violations, such as mass surveillance, the spread of hate speech, and information manipulation. The rapid development of digital technology has outstripped the ability of international law to regulate it, creating a significant legal gap where human rights in the digital space are not adequately protected. This challenge is further complicated by the cross-border nature of the internet and other digital technologies. This journal discusses international legal issues related to the protection of human rights in the digital era. This research uses a normative legal research method with a case study approach, analyzing international legal documents such as international treaties, UN resolutions, and international court jurisprudence. This journal also analyzes case studies related to human rights violations in the digital era. The results of the study indicate that a more comprehensive international legal framework, clear international standards, and effective law enforcement efforts are needed to protect human rights in the digital space. The proposed recommendations include developing a comprehensive legal framework, enhancing international cooperation, strengthening law enforcement efforts, increasing public awareness, and civil society participation.